Perilaku Penggunaan E-Wallet sebagai Alat Pembayaran di Kalangan Mahasiswa Universitas 17 Agustus 1945 Surabaya: Ditinjau dari Aspek Kemudahan, Keamanan, dan Promosi - Angelina Wijaya Tan; Hwihanus, Hwihanus (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the influence of ease of use, security, and promotion on e-wallet usage behavior among students at Universitas 17 Agustus 1945 Surabaya. The background of this study stems from the increasing adoption of e-wallets among students, which is not always accompanied by consistent usage behavior, thus requiring an understanding of the factors that encourage or hinder actual usage. This study uses a quantitative approach with an explanatory method. Data were collected through a Likert scale questionnaire distributed to students who use e-wallets, then analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that ease of use has a positive and significant effect on e-wallet usage behavior. This means that the easier the application is to learn, understand, and use, the higher the intensity of student usage. Conversely, the variables of security and promotion do not have a significant partial effect, even though both have a positive direction of influence.